2020
DOI: 10.1111/peps.12431
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the relationship between applicant race and accrued recruitment source information: Implications for applicant withdrawal and test performance

Abstract: We examine the role of accrued recruitment source diagnosticity (i.e., cumulative information from recruitment sources) and show its importance in enhancing diversity in recruitment and selection. First, based on social network and homophily theories, we propose that racial minority candidates will be less likely to use diagnostic recruitment sources, and this lack of use contributes to less organizational attraction and greater withdrawal. Second, based on the realism hypothesis, we theorize that racial diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 84 publications
1
15
0
Order By: Relevance
“…Some beliefs we identified complement those found elsewhere (perceived usefulness, perceived ease of use and self-efficacy in Lin, 2010; comfort in Wanberg et al. , 2000; job and hiring process information in McFarland and Kim, 2021), strengthening the importance of these factors. Others, such as personalization, extend the domain.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Some beliefs we identified complement those found elsewhere (perceived usefulness, perceived ease of use and self-efficacy in Lin, 2010; comfort in Wanberg et al. , 2000; job and hiring process information in McFarland and Kim, 2021), strengthening the importance of these factors. Others, such as personalization, extend the domain.…”
Section: Discussionsupporting
confidence: 70%
“…** p < 0.01. *** p < 0.0033 inMcFarland and Kim, 2021), strengthening the importance of these factors.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…This is in line with the prescreening hypothesis that job incumbent referrers are able to screen potential applicants and recommend only the best because they know the job better. McFarland and Kim's (2021) recent research found, consistent with the homophily principle, that non‐white job seekers used less diagnostic recruitment sources overall, reducing minority attraction and thus explaining DEI shortcomings. For example, white individuals tended to use diagnostic sources such as word of mouth more, likely because such information is more available to them through their social networks.…”
Section: Key Recruitment Outcomesmentioning
confidence: 92%
“…This evolution continues today, as evidenced by the dominant themes of recruitment research in the field, which are reflective of the disruptive changes in business and society (Ployhart et al, 2017). First, in the area of recruitment and diversity, researchers are studying how recruitment messages can be used to increase applicant diversity and reduce adverse impacts that may be disadvantaging minority candidates (Campion et al, 2019; McFarland & Kim, 2021; Van Iddekinge et al, 2016). Second, in the area of recruitment practices and technology, significant effort is being put into investigating how digital communication tools like social media have revolutionized the practice of recruitment.…”
Section: A Brief History Of Talent Acquisitionmentioning
confidence: 99%